Evaluation of the Polarity in Binary Liquid Mixtures as a Function of Volume Fraction - Jyoti, Nirmal; S. Meena, Anoop; Beniwal, Vijay (Asian Journal of Chemistry, 2023)
The variation of solvatochromic polarity parameters as a function of mole fraction data may not represent the realistic environment of the solvatochromic probe molecule. This is because of the fact that the solvation environment of the solvatochromic probe molecules is not only determined by the number of individual solvent molecules around it but also by the size of those individual solvent molecules. In this regard we wish to understand the variation of ENT polarity parameter of binary liquid mixtures as a fuction of volume fractions. Representation of the ENT parameter as a function of volume fraction data leads to a completely different dataset for binary liquid mixtures where water is used as one of the solvents. These mixtures usually display negative deviations from linearity for the ENT values, when ENT values are plotted as a function of mole fraction values of the solvents. On the other hand, if the ENT values are plotted as a function of volume fraction values of the solvents in binary liquid mixtures containing water, these deviations are minimized to a large extent and even reversed to the positive deviations in some of these mixtures. This study gives an insight into a long lasting problem of understanding the negative deviations of the ENT values from linearity observed in binary liquid mixtures of water, as these deviations are either minimized or reversed into positive deviations when ENT values are plotted versus volume fraction of solvents. This study opens up a whole new discussion about the solvatochromic data of the solvent mixtures, whether this data must be represented as a function of mole fraction values or as a function of volume fraction of the solvents. The representation of the solvatochromic data as a function of volume fraction of solvents might lead to new insights in studying the solute-solvent interactions in binary solvent mixtures.